2021
DOI: 10.9734/ijecc/2021/v11i330371
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Pollution Status of Lagos Coastal Waters and Sediments, using Physicochemical Characteristics, Contamination Factor, Nemerow Pollution Index, Ecological Risk and Potential Ecological Risk Index

Abstract: The heavy metals and physicochemical properties of Lagos coastal waters and sediments, Southwestern Nigeria were investigated in 5 stations (station 1-5), to determine their levels, distributions and pollution index. The observed ranges of physicochemical characteristics from the study area are: dissolved oxygen (DO): 2.15-11.3 mg/L; pH: 6-7.7; temperature (Temp): 28.05-29.25°C; biochemical oxygen demand (BOD): 1.6-110.1 mg/L; electrical conductivity (EC): 1.8-29.8 mS/cm; salinity (SAL): 0.02-2.05ppt; total di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Thus, the introduction of non-indigenous species through ballast water can lead to competition with native species, the decline or extinction of indigenous species, and disruption of the ecosystem (Hess-Erga et al, 2019). The conditions of the Lagos Coastal Waters reveals low dissolved oxygen and high biochemical oxygen demand at certain stations (Ajani et al, 2021). Nkwoji et al (2020) revealed in their study of the coastal Lagos Lagoon that the inflow of pollutants from land-based sources resulted in degraded water quality, and low diversity and abundance of benthic macroinvertebrates.…”
Section: Comparative Analysis Of Ballast Tank Parameters Across Diffe...mentioning
confidence: 99%
“…Thus, the introduction of non-indigenous species through ballast water can lead to competition with native species, the decline or extinction of indigenous species, and disruption of the ecosystem (Hess-Erga et al, 2019). The conditions of the Lagos Coastal Waters reveals low dissolved oxygen and high biochemical oxygen demand at certain stations (Ajani et al, 2021). Nkwoji et al (2020) revealed in their study of the coastal Lagos Lagoon that the inflow of pollutants from land-based sources resulted in degraded water quality, and low diversity and abundance of benthic macroinvertebrates.…”
Section: Comparative Analysis Of Ballast Tank Parameters Across Diffe...mentioning
confidence: 99%
“…Studies have demonstrated the occurrence of the contamination of sediments by trace metals caused by human activities, urbanization and industrialization [ 43 , 57 , 58 , 59 , 60 ]; agriculture [ 61 , 62 ]; and mining [ 63 , 64 , 65 ].…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al [8] used principal component analysis to evaluate the water quality of lakes for pH, conductivity, Ca 2+ , K + , Na + , Cl − , NO 3 − , SO 4 2− , CO 3 2− and other ions, with good results. Ajani et al [9] used the Nemerow pollution index to evaluate the integrated pollution status of sediments in the water zone. Principal component analysis (PCA) can avoid subjective arbitrariness and objectively determine the weights of each index for quantitative studies.…”
Section: Introductionmentioning
confidence: 99%